IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM MELALUI PROGRAM KEGIATAN EKSTRAKURIKULER KEAGAMAAN DI SMAN 1 PURWODADI KABUPATEN MUSI RAWAS - Suhadak Suhadak (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
This research was motivated by the fact that the learning outcomes of Islamic education is not optimal, it is expectedto strengthen Islamic education with better religious extracurricular activities.This study aimed at describing Islamic EducationCurriculum Implementation Through religious Extracurricular activities program at SMAN 1 Purwodadi Musi Rawas Which isconsisting of program and implementation, The Implementation and determination of the supporting factors and thus becomemore directed to realize the vision and mission of the school. Method and the type of the research is descriptive qualitative.Subjects were principals, teachers and students of Islamic religious education class x that is active in religious eksrakurikulerSpiritual Islam. Data collection techniques used in this research were observation, interviews, and documentation. Data analysisis done by reducing the data (data reduction), data presentation (display data), and conclusion (Verification Data). Testingthe validity of the data using observations extension, increase endurance, and triangulation of data. Based on the results, itcan be concluded that there are two results about How Curriculum Implementation PAI through religious extracurricularactivities program in SMA Negeri 1 PurwodadiMusi-Rawas namely: The implementation of curriculum development at PAIbasedon extracurricular activity is by designing some of the programs that the program is considered to be able to cover thepurposes of education PAI generally or specifically private lodging which these objectives can not be achieved through theactivities of teaching (Teaching and Learning) in the class in which the time of these activities are very limited. The activitieincludes such things as nasyid activities, peer tutoring, tahsinqiroah, qiroatul quran and many other activities that researchersconsider it as a manifestation of Islamic Religion educational purposes in schools.The activity is really manageable neatly andinvolves several important elements that will make this event run effectively. And of the way of the success of these activitiesaccording to the researchers is the existence of solid team work, even though this is an activity of PAI teacher but the entirestakeholders fully involved in this case. That is one reason why these activities go well.